To solve the equation, we need to isolate the variable x.
Starting with the equation:
5/3x + 11/3 = -4/3
Subtract 11/3 from both sides of the equation:
5/3x = -4/3 - 11/3
Simplifying the right side of the equation:
5/3x = -15/3
Now, multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3x) = (3/5)(-15/3)
The 3's cancel out on the left side, and the negative signs multiply on the right side:
x = -9/5
Therefore, the solution to the equation 5/3x + 11/3 = -4/3 is x = -9/5.
the equation is 5/3x + 11/3 = -4/3
is solved as follows. Supply the correct numbers to complete the solution.
15 answers
wrong
Apologies for the error. Let's solve the equation correctly.
The equation is:
5/3x + 11/3 = -4/3
Step 1: Subtract 11/3 from both sides of the equation:
5/3x = -4/3 - 11/3
Simplifying the equation:
5/3x = -15/3
Step 2: Simplify the right side of the equation:
-15/3 can be simplified as -5.
So we have:
5/3x = -5
Step 3: Multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
3/5 * (5/3x) = 3/5 * (-5)
Simplifying:
(3/5) * (5/3) * x = -15/5
The 5's and 3's cancel out, leaving us with:
1x = -15/5
Multiplying -15/5 by 1 gives us:
x = -15/5
Simplifying the fraction:
x = -3
Therefore, the solution to the equation 5/3x + 11/3 = -4/3 is x = -3.
The equation is:
5/3x + 11/3 = -4/3
Step 1: Subtract 11/3 from both sides of the equation:
5/3x = -4/3 - 11/3
Simplifying the equation:
5/3x = -15/3
Step 2: Simplify the right side of the equation:
-15/3 can be simplified as -5.
So we have:
5/3x = -5
Step 3: Multiply both sides of the equation by the reciprocal of 5/3, which is 3/5:
3/5 * (5/3x) = 3/5 * (-5)
Simplifying:
(3/5) * (5/3) * x = -15/5
The 5's and 3's cancel out, leaving us with:
1x = -15/5
Multiplying -15/5 by 1 gives us:
x = -15/5
Simplifying the fraction:
x = -3
Therefore, the solution to the equation 5/3x + 11/3 = -4/3 is x = -3.
the equation is 0.24x - 0.74 = -1.1 is solved as follows. Supply the correct numbers to complete the solution.
To solve the equation 0.24x - 0.74 = -1.1, we can follow these steps:
Step 1: Add 0.74 to both sides of the equation:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
Simplifying the left side of the equation:
0.24x = -1.1 + 0.74
0.24x = -0.36
Step 2: Divide both sides of the equation by 0.24 to isolate x:
(0.24x)/0.24 = (-0.36)/0.24
Simplifying:
x = (-0.36)/0.24
Step 3: Divide the numbers:
x = -1.5
Thus, the solution to the equation 0.24x - 0.74 = -1.1 is x = -1.5.
Step 1: Add 0.74 to both sides of the equation:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
Simplifying the left side of the equation:
0.24x = -1.1 + 0.74
0.24x = -0.36
Step 2: Divide both sides of the equation by 0.24 to isolate x:
(0.24x)/0.24 = (-0.36)/0.24
Simplifying:
x = (-0.36)/0.24
Step 3: Divide the numbers:
x = -1.5
Thus, the solution to the equation 0.24x - 0.74 = -1.1 is x = -1.5.
what is the solution of the equation -8x + 13 = -19?
To solve the equation -8x + 13 = -19, we can follow these steps:
Step 1: Subtract 13 from both sides of the equation:
-8x + 13 - 13 = -19 - 13
Simplifying the left side of the equation:
-8x = -19 - 13
-8x = -32
Step 2: Divide both sides of the equation by -8 to isolate x:
(-8x)/(-8) = (-32)/(-8)
Simplifying:
x = 4
Thus, the solution to the equation -8x + 13 = -19 is x = 4.
Step 1: Subtract 13 from both sides of the equation:
-8x + 13 - 13 = -19 - 13
Simplifying the left side of the equation:
-8x = -19 - 13
-8x = -32
Step 2: Divide both sides of the equation by -8 to isolate x:
(-8x)/(-8) = (-32)/(-8)
Simplifying:
x = 4
Thus, the solution to the equation -8x + 13 = -19 is x = 4.
what is the solution of the equation 11 - 4x = -9
To solve the equation 11 - 4x = -9, we can follow these steps:
Step 1: Subtract 11 from both sides of the equation:
11 - 4x - 11 = -9 - 11
Simplifying the left side of the equation:
-4x = -20
Step 2: Divide both sides of the equation by -4 to isolate x:
(-4x)/(-4) = (-20)/(-4)
Simplifying:
x = 5
Thus, the solution to the equation 11 - 4x = -9 is x = 5.
Step 1: Subtract 11 from both sides of the equation:
11 - 4x - 11 = -9 - 11
Simplifying the left side of the equation:
-4x = -20
Step 2: Divide both sides of the equation by -4 to isolate x:
(-4x)/(-4) = (-20)/(-4)
Simplifying:
x = 5
Thus, the solution to the equation 11 - 4x = -9 is x = 5.
what is the solution of the equation 2/5x + 4 = 1/5?
To solve the equation 2/5x + 4 = 1/5, we can follow these steps:
Step 1: Subtract 4 from both sides of the equation:
2/5x + 4 - 4 = 1/5 - 4
Simplifying the left side of the equation:
2/5x = 1/5 - 4
Step 2: Simplify the right side of the equation:
1/5 - 4 = -19/5
So we have:
2/5x = -19/5
Step 3: Multiply both sides of the equation by the reciprocal of 2/5, which is 5/2:
(5/2)*(2/5x) = (5/2)*(-19/5)
Simplifying:
x = -19/2
Thus, the solution to the equation 2/5x + 4 = 1/5 is x = -19/2.
Step 1: Subtract 4 from both sides of the equation:
2/5x + 4 - 4 = 1/5 - 4
Simplifying the left side of the equation:
2/5x = 1/5 - 4
Step 2: Simplify the right side of the equation:
1/5 - 4 = -19/5
So we have:
2/5x = -19/5
Step 3: Multiply both sides of the equation by the reciprocal of 2/5, which is 5/2:
(5/2)*(2/5x) = (5/2)*(-19/5)
Simplifying:
x = -19/2
Thus, the solution to the equation 2/5x + 4 = 1/5 is x = -19/2.
what is the solution of the equation 5/3 - 2x = 1/6?
To solve the equation 5/3 - 2x = 1/6, we can follow these steps:
Step 1: Subtract 5/3 from both sides of the equation:
5/3 - 2x - 5/3 = 1/6 - 5/3
Simplifying the left side of the equation:
-2x = 1/6 - 5/3
Step 2: Simplify the right side of the equation:
1/6 - 5/3 can be simplified as -14/6.
So we have:
-2x = -14/6
Step 3: Multiply both sides of the equation by the reciprocal of -2, which is -1/2:
(-1/2)*(-2x) = (-1/2)*(-14/6)
Simplifying:
x = 7/6
Thus, the solution to the equation 5/3 - 2x = 1/6 is x = 7/6.
Step 1: Subtract 5/3 from both sides of the equation:
5/3 - 2x - 5/3 = 1/6 - 5/3
Simplifying the left side of the equation:
-2x = 1/6 - 5/3
Step 2: Simplify the right side of the equation:
1/6 - 5/3 can be simplified as -14/6.
So we have:
-2x = -14/6
Step 3: Multiply both sides of the equation by the reciprocal of -2, which is -1/2:
(-1/2)*(-2x) = (-1/2)*(-14/6)
Simplifying:
x = 7/6
Thus, the solution to the equation 5/3 - 2x = 1/6 is x = 7/6.
Answer to whole quick check:
Q1. -3x = -12
x = 4
Q2. 10x = -25
x = -2.5
Q3. x = 2
Q4. 5/3x = -5
x = -3
Q5. 0.24x = -0.36
x = 1.5
There have a good day 👴🏻👴🏻
Q1. -3x = -12
x = 4
Q2. 10x = -25
x = -2.5
Q3. x = 2
Q4. 5/3x = -5
x = -3
Q5. 0.24x = -0.36
x = 1.5
There have a good day 👴🏻👴🏻
Answers to the second Quick check:
Q1. 4
Q2. 5
Q3. -19/2
Q4. 3/4
Q5. -30.6
All 100%
Have a good day 🥱🥱
Q1. 4
Q2. 5
Q3. -19/2
Q4. 3/4
Q5. -30.6
All 100%
Have a good day 🥱🥱